2021
DOI: 10.1111/jfbc.13779
|View full text |Cite
|
Sign up to set email alerts
|

Study on the domain selective inhibition of angiotensin‐converting enzyme (ACE) by food‐derived tyrosine‐containing dipeptides

Abstract: In this article, the selective inhibition of several tyrosine‐containing dipeptides on N and C domain of ACE (angiotensin‐converting enzyme) was studied, and the interaction mode of ACE and inhibitors was simulated by molecular docking. MTT assay was used to detect the effect of dipeptide on human umbilical vein endothelial cells (HUVEC). The results showed that the food‐derived dipeptides AY (Ala‐Tyr), LY (Leu‐Tyr), and IY (Ile‐Tyr) containing tyrosine at the C‐terminal were favorable structures for selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…V max was concentration-dependent while K m was relatively constant suggesting that ACE inhibition by L- m -tyrosine is a non-competitive inhibition. Similar to the present study, several tyrosine-containing dipeptides noncompetitively inhibited ACE [ 44 ]. In previous reports, ACE inhibitors obtained by hydrolysis of marine products, such as squid and tuna noncompetitively inhibited ACE [ 52 , 53 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…V max was concentration-dependent while K m was relatively constant suggesting that ACE inhibition by L- m -tyrosine is a non-competitive inhibition. Similar to the present study, several tyrosine-containing dipeptides noncompetitively inhibited ACE [ 44 ]. In previous reports, ACE inhibitors obtained by hydrolysis of marine products, such as squid and tuna noncompetitively inhibited ACE [ 52 , 53 ].…”
Section: Resultssupporting
confidence: 88%
“…ACE inhibitors of natural origin were present in carp scales, salmon processing by-products, and aosa-derived substances [ 41 , 42 , 43 ]. Previous studies have reported tyrosine-containing dipeptides [ 39 , 44 , 45 ] and tripeptides over [ 46 , 47 ] ACE inhibitory peptides. Inhibitory dipeptides with a tyrosine residue at the C-terminus are effective [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, treatment with carnosine or anserine prevented alterations of renal function in diabetic (db/db) mice [29][30][31]. Additionally, for proline-containing dipeptides the biological activities seem to be not only based on the free amino acid alone [1]; for Tyr-containing dipeptides [32] an inhibitory effect on ACE activity has been demonstrated, and Tyr-Asp improves plant tolerance to oxidative stress by directly interfering with glucose metabolism [33]. Gly-containing dipeptides can provide osmoregulation in preimplantation embryos [34].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, a variety of small peptides derived from food sources such as milk, egg, fish, and rice have been found to exhibit potential antihypertensive activity by inhibiting ACE 21,22 . In particular, the food‐derived tyrosine/tryptophan‐containing dipeptides have recently been found as the C‐domain selective inhibitors of ACE 23,24 . These selective peptide inhibitors possess low toxicity and high biocompatibility, and thus serve as the good antihypertensive peptide (AHP) candidates of functional medicines to lower blood pressure and reduce the mortal risk in patients with HTN syndromes.…”
Section: Introductionmentioning
confidence: 99%